Analisis Akurasi ChatGPT dalam Mengkaji Validitas Sanad dan Matan Hadis - Amalia, Yeni (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2024)
The emergence of ChatGPT as a new technology capable of addressing various religious issues, particularly in Hadith studies, presents new challenges for Hadith scholars in preserving the authenticity and sanctity of Hadith. This study aims to evaluate the accuracy of ChatGPT in assessing the validity of sanad and matan by comparing its analysis of five selected hadiths with the book Jawami’ul Kalim. Using a descriptive-analytical method, the research refers to the concept of